Experimental investigation of heat transfer and pressure drop of fin and tube heat exchanger under dry and wet conditions - Bozkula, Gokhan; Demir, Hakan (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2022)
The heat transfer and pressure drop characteristics of nine flat plate finned tube heat exchangers have been experimentally investigated under dry and wet conditions. The effect of five parameters is evaluated for wet conditions: number of tube row (2, 4, 6), fin pitch (2, 3, 4 mm), frontal air velocity (1, 2, 3 m/s), temperature (25, 30, 35 degrees C), and relative humidity (60, 70, 80). The Box-Behnken Design (BBD) is used to determine minimum candidate test points of the experimental studies, and more experiments have been carried out to determine the effects more sensitively. For nine heat exchangers, the effect of frontal air velocity (1, 2, 3 m/s) is evaluated for dry conditions. (The Reynolds number ranged from 300 to 2150 for both conditions.) Response Surface Model (RSM) has been used to evaluate the Colburn j factor and Fanning friction f factor for dry and wet conditions. The results show that the j factor decreases with increasing front air velocity and number of tube rows, while the j factor increases with increasing fin pitch, air temperature, and relative humidity for wet conditions. In addition, the f factor decreases with increasing front air velocity, number of tube rows and fin pitch, while the f factor increases with increasing air temperature and relative humidity. For dry conditions, the j factor decreases with increasing front air velocity and number of tube rows, while the j factor increases with increasing fin pitch. In addition, the f factor decreases with increasing front air velocity, number of tube rows, while the f factor increases with increasing fin pitch. The j factor and f factor values are higher under wet conditions than dry conditions. Three correlations are proposed for the j and f factors under dry and wet conditions. For wet conditions, the best mean deviation for the j factor is 8.3%, whereas the best mean deviation for the f factor is 10.9%. For dry conditions, the best mean deviation for the j factor is 8.3%, whereas the best mean deviation for the f factor is 8.2%. The experimental results are compared with the proposed and literature correlations. Compared to the correlations obtained in literature studies using similar geometric parameters in the study, the proposed correlation has gave better results. Even at the values of geometric parameters which literature correlations are failed, the proposed correlations has gave good results.
Keywords: Fin and tube heat exchanger (FTHE); Heat and mass transfer; Colburn j-factor; Fanning friction f factor; FRICTION CHARACTERISTICS; MASS-TRANSFER; TRANSFER COEFFICIENTS; TRANSFER PERFORMANCE; OPTIMIZATION; PREDICTION; Thermodynamics; Engineering